2017
DOI: 10.1159/000475971
|View full text |Cite
|
Sign up to set email alerts
|

ZNF667 Serves as a Putative Oncogene in Human Hepatocellular Carcinoma

Abstract: Background/Aims: Zinc finger protein 667 (ZNF667) is a member of C2H2 zinc finger protein family. For the first time, we aim to analyze the expression pattern of ZNF667 in hepatocellular carcinoma (HCC) tissues; to explore its role in HCC tumorigenesis. Methods: Immuno-histochemistry was carried out to characterize the ZNF667 expression in paraffin-embedded HCC samples. The relationship between ZNF667 expression and the clinical, pathological data of the patients were analyzed. Human normal hepatocyte cells LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…LncRNAs can modulate gene expression by binding to chromatin regulators and interfering with the functions of RNAs, thereby exercising their effects on cellular responses (Liao et al , ). Zinc finger protein 667 (ZNF667) is an lncRNA capable of regulating numerous cellular processes, such as cell proliferation, migration, and invasion (Cheng et al , ). ZNF667‐antisense RNA 1 (ZNF667‐AS1) is documented as a biomarker and a potential therapeutic target for CC (Zhao et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can modulate gene expression by binding to chromatin regulators and interfering with the functions of RNAs, thereby exercising their effects on cellular responses (Liao et al , ). Zinc finger protein 667 (ZNF667) is an lncRNA capable of regulating numerous cellular processes, such as cell proliferation, migration, and invasion (Cheng et al , ). ZNF667‐antisense RNA 1 (ZNF667‐AS1) is documented as a biomarker and a potential therapeutic target for CC (Zhao et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Those with low expression of ZNF667 in HNSC tend to had poor survival rate, as indicated by GEPIA (Additional file 2: Figure S1D), with the same trend of ZNF667-AS1. However, Ke Cheng et al reported that ZNF667 was up-regulated in hepatocellular carcinoma and served as a putative oncogene [15]. Given genes are expressed in a cell- and tissue-specific manner, the different roles of ZNF667 in different cancers may be explained by the different basic expression level in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF667 was suggested to play an important role in oxidative stress [12], and was an anti-apoptotic factor in some conditions [13, 14]. Recently, it was reported that ZNF667 served as a putative oncogene in human hepatocellular carcinoma [15]. The expression of ZNF667 in LSCC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As a head-to-head lncRNA, ZNF667-AS1 and its antisense transcript ZNF667 are both located in 19q13.43. The role of ZNF667-AS1 and ZNF667 has been reported in several types of cancers 1114,16,24 ; however, the functional role of them in ESCC has not been clarified. ZNF667-AS1 was first reported in a study using microarray analysis to analyze the changed genes in immortalized human mammary epithelial cells (HMEC), and ZNF667-AS1 was found to be expressed in all normal finite lifespan human cells examined to date, and was downregulated or inactivated in immortalized HMEC 11 .…”
Section: Discussionmentioning
confidence: 99%